RELATIONSHIP BETWEEN MATERNAL PSYCHOSOCIAL STATUS AND TREGNANCY OUTCOMES - Dabbaghi, F; Sadeghi, H; Jahaanfar, SH; Haghani, H (Iran University of Medical Sciences, 2001)
Background : Pregnant women with high level of anxiety are likely to give birth to babies who are irritable, restless, have sleep disorders and low birth weight.   Objective : To determine the relation of psychosocial status of women during pregnancy and pregnancy outcomes.   Design : This was a comparative study. Data were collected using a questionnaire.   Samples : 360 subject nuliparas to multiparas 4, were selected through consequative sampling, 180 in each group (appropriate and inappropriate psycholocial status).   Results : There was a relation between psychosocial status of mothers and LBW (p=0.005), IUGR (p=0.028) and preterm labor (p=0.000).   Conclusion : Emotional support by family and health care providers should be targeted at women with poor psychosocial status during pregnancy in order to decrease their emotional distress and to enhance their self- esteen and self- confidence.